No greens in the forest? Note on the limited consumption of greens in the Amazon - Dias, Terezhina; Fleury, Marie; Katz, Esther; López Garcés, Claudia Leonor; Miller, Robert P.; Moreira, Elaine; Oliveira, Zelandes; Payê, Valeria; Silva, Franklin (Polish Botanical Society, 2021)
The consumption of greens is reported as being very minor among Amazonian Indians. The authors of this article present a new review of this subject, based on fieldwork with Amerindians and other populations in different parts of the Brazilian Amazon and French Guiana. Written sources on Brazilian, Peruvian, Columbian and Venezuelan Amazon were also reviewed. The consumption of cultivated, semi-cultivated and wild species of greens was taken into account here, as the data specific to wild greens is very scarce. It is confirmed that greens are not commonly eaten among native Amazonians and that some ethnic groups do not consume them at all. The consumed species are usually young shoots of weeds or cassava leaves. Common in the Belém region are some specific aromatic plants, which have been diffused to other parts of the Amazon, together with introduced plants such as kale and coriander. Migrants from Northeastern Brazil settled in the Amazon consume some cultivated greens, especially aromatic plants. Maroons are the ones who use more greens in their diet. Native Amazonian people, who supplement agriculture with game and fish, follow a hunter-gatherer pattern, preferring wild fruit and tubers to greens.